Comparison of Different Sampling Strategies and Laboratory Methods for the Detection of C. jejuni and C. coli from Broiler Flocks at Primary Production. (30th August 2012) - Vidal, A. B.; Rodgers, J.; Arnold, M.; Clifton‐Hadley, F.
Abstract : Summary The objective of the study was to evaluate the performance of different combinations of sample type, transport medium and culture methods for the recovery of Campylobacter jejuni and C. coli from broiler flocks at primary production. Boot swabs moistened with one of four different transport media [maximum recovery diluent ( n  =   120), Exeter broth (EX) ( n  =   120), buffered peptone water ( n  =   120) and modified semi‐solid Cary‐Blair ( n  =   120)], caecal samples ( n  =   40) and faecal samples ( n  =   120) from 40 broiler flocks were compared and sensitivity estimates obtained using a Bayesian model. Samples were cultured onto mCCDA before and after enrichment in EX and incubated microaerobically at 41.5°C. Campylobacter suspect colonies were identified to the species level by multiplex PCR. Results from the Bayesian model indicated that boot swabs after enrichment had higher sensitivity (90–94%) than caecal contents before or after enrichment (84% and 89%, respectively) and faecal samples after enrichment (82%) for the detection of Campylobacter spp., although these differences were not statistically significant. Enrichment significantly increased the sensitivity of boot swab and caecal samples for detection of Campylobacter spp. and C. jejuni, respectively. However, the enrichment of caecal samples resulted in a significant decrease in the sensitivity of these samples for detection of C. coli . There was much greater variation in the sensitivity estimates of the methods for detecting C. coli than for C. jejuni, and the ranking of methods was different between the two species. Boot swabs gave the best sensitivity values for detection of C. jejuni, and enrichment culture of faecal samples was the most sensitive method for detection of C. coli .